2022
DOI: 10.1155/2022/3129155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitexin, a Natural Flavonoid Glycoside, on the Proliferation, Invasion, and Apoptosis of Human U251 Glioblastoma Cells

Abstract: Glioblastoma is a highly aggressive brain tumor characterized by high recurrence and poor prognosis. Vitexin has shown activities against esophageal, liver, lung, colorectal, and ovarian cancers; however, there is little knowledge on the activity of vitexin against glioblastoma. This study was therefore designed with aims to examine the effects of vitexin on proliferation, invasion, and apoptosis of human U251 glioblastoma cells and explore the underlying molecular mechanisms using mRNA sequencing and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Previous study has shown that vitexin suppressed cell proliferation and metastasis of leukaemia, brain tumors, esophageal cancer breast and oral carcinoma [6]. Vitexin reduced activation of Phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling to repress proliferation of hepatocellular carcinoma, renal cell carcinoma, non-small-cell lung cancer, and glioblastoma [23]. Tumor growth of cervical tumor xenograft was also suppressed by vitexin [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that vitexin suppressed cell proliferation and metastasis of leukaemia, brain tumors, esophageal cancer breast and oral carcinoma [6]. Vitexin reduced activation of Phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling to repress proliferation of hepatocellular carcinoma, renal cell carcinoma, non-small-cell lung cancer, and glioblastoma [23]. Tumor growth of cervical tumor xenograft was also suppressed by vitexin [14].…”
Section: Discussionmentioning
confidence: 99%
“…The grid box size was set using the software AutoDock Vina version 1.5.6, and the docking results were visualized using the PyMOL software [ 21 ]. A negative binding energy indicates a high likelihood of the binding between the ligand and receptor [ 15 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The grid box size was set using the software AutoDock Vina version 1.5.6, and the docking results were visualized using the PyMOL software [21]. A negative binding energy indicates a high likelihood of the binding between the ligand and receptor [15,22,23]. officinalis, 2 active ingredients of A. sinensis, 13 active ingredients of P. lactiflora, 12 active ingredients of T. terrestris, and 4 active ingredients of C. haliotidis.…”
Section: Molecular Docking Verificationmentioning
confidence: 99%
“…Vitexin has a variety of biological activities, including antioxidant, anti-inflammatory, neuronal protection, and cardio protection, as well as fat reduction, glucose metabolism, and hepatoprotective effects ( 17 ). Studies have shown that vitexin has anti-proliferative effects on a variety of tumor cells ( 18 ), such as glioma ( 19 ), liver cancer ( 20 ), nasopharyngeal carcinoma ( 21 ), and colon cancer, with a wide range of tumor therapeutic effects. More importantly, several studies have pointed out that vitexin can prevent colitis-associated carcinogenesis in mice by regulating macrophage polarization ( 22 ) and effectively inhibit the proliferation of colorectal cancer in vivo or in vitro ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%